Peripheral neuropathy in patients with CPEO associated with single and multiple mtDNA deletions - Lehmann, Diana (Neurol Genet, 2016)
OBJECTIVE: To characterize peripheral nerve involvement in patients with chronic progressive external ophthalmoplegia (CPEO) with single and multiple mitochondrial DNA (mtDNA) deletions, based on clinical scores and detailed nerve conduction studies. METHODS: Peripheral nerve involvement was prospectively investigated in 33 participants with CPEO (single deletions n = 18 and multiple deletions n = 15). Clinically, a modified Total Neuropathy Score (mTNS) and a modified International Cooperative Ataxia Rating Scale (mICARS) were used. Nerve conduction studies included Nn. suralis, superficialis radialis, tibialis, and peroneus mot. Early somatosensory evoked potentials were obtained by N. tibialis stimulation. RESULTS: Participants with multiple deletions had higher mTNS and mICARS scores than those with single deletions. Electrophysiologically in both sensory nerves (N. suralis and N. radialis superficialis), compound action potential (CAP) amplitudes and nerve conduction velocities were lower and mostly abnormal in multiple deletions than those in single deletions. Early somatosensory evoked potentials of N. tibialis revealed increased P40 latencies and decreased N35-P40 amplitudes in multiple deletions. Both sensory nerves had higher areas under the receiver operating characteristic curves for the decreased CAP amplitudes than the 2 motor nerves. The N. suralis had the best Youden index, indicating a sensitivity of 93.3% and a specificity of 72.2% to detect multiple deletions. CONCLUSIONS: Peripheral nerve involvement in participants with multiple mtDNA deletions is an axonal type of predominant sensory neuropathy. This is clinically consistent with higher mTNS and mICARS scores. Sensory nerve involvement in participants with multiple deletions was not correlated with age at onset and duration of disease.